Exploring Bone Morphogenetic Protein-2 and -4 mRNA Expression and Their Receptor Assessment in a Dynamic In Vitro Model of Vascular Calcification - Manuela Cabiati; Federico Vozzi; Elisa Ceccherini; Letizia Guiducci; Elisa Persiani; Ilaria Gisone; Agnese Sgalippa; Antonella Cecchettini; Silvia Del Ry (Cells)
Background: Vascular calcification (VC) is a dynamic, tightly regulated process driven by cellular activity and resembling the mechanisms of bone formation, with specific molecules playing pivotal roles in its progression. We aimed to investigate the involvement of the bone morphogenic proteins (BMP-2, BMP-4, BMPR-1a/1b, and BMPR-2) system in this process. Our study used an advanced in vitro model that simulates the biological environment of the vascular wall, assessing the ability of a phosphate mixture to induce the osteoblastic switch in human coronary artery smooth muscle cells (HCASMCs). Methods: HCASMCs were grown in mono- and co-culture with human coronary artery endothelial cells (HCAECs) in a double-flow bioreactor (LiveBox2 and IVTech), allowing static and dynamic conditions through a peristaltic pump. The VC was stimulated by incubation in a calcifying medium for 7 days. A BMP system Real-Time PCR was performed at the end of each experiment. Results: In monocultures, BMP-2 expression increased in calcified HCASMCs in static (p = 0.01) and dynamic conditions. BMP-4 and the biological receptors were expressed in all the experimental settings, increasing mainly in dynamic flow conditions. In co-cultures, we observed a marked increase in BMP-2 and BMP-4, BMPR-1a (p = 0.04 and p = 0.01, respectively), and BMPR-2 (p = 0.001) in the calcifying setting mostly in dynamic conditions. Conclusions: The increase in BMP-2/4 in co-culture suggests that these genes might promote the switch towards an osteogenic-like phenotype, data also supported by the rise of both BMPR-1a and BMPR-2. Thus, our findings provide insights into the mechanisms by which dynamic co-culture modulates the BMP system activation in an environment mimicking in vivo VC’s cellular and mechanical characteristics.